2014
DOI: 10.1017/s1368980014001426
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet-related stimulation of sweetness desire is greater in women than in men despite high vegetable intake

Abstract: Objective: To examine the effects of lunches with different dietary energy densities on food preferences between genders. Design: Randomized crossover study. Participants were administered the following packed test meals once weekly on a specified day during six sessions: control (150 g of rice with a sautéed beef entrée containing 40 g of raw beef and 240 g of vegetables), high-meat/low-rice, low-vegetable, medium-fat/low-vegetable, high-fat and high-fat/low-vegetable meals. Subjective levels of sensory prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A "set of sweetened foods or beverages" was defined as one or more variations of the same food or beverage, tested in the same study population, sweetened with the same sweetener (i.e., sugar or NNS), but differing only in the level of sweetness. In the remaining eight studies [25][26][27][28][29][30][31][32], sweetness preference was assessed without having subjects sample and rate a sweetened food or beverage. For example, Mizuta et al [26] requested study participants with different leptin and leptin gene polymorphisms to score from 1 ("I hate them") to 5 ("I love them") when asked, "Do you like things that taste sweet?"…”
Section: Key Study Characteristicsmentioning
confidence: 99%
“…A "set of sweetened foods or beverages" was defined as one or more variations of the same food or beverage, tested in the same study population, sweetened with the same sweetener (i.e., sugar or NNS), but differing only in the level of sweetness. In the remaining eight studies [25][26][27][28][29][30][31][32], sweetness preference was assessed without having subjects sample and rate a sweetened food or beverage. For example, Mizuta et al [26] requested study participants with different leptin and leptin gene polymorphisms to score from 1 ("I hate them") to 5 ("I love them") when asked, "Do you like things that taste sweet?"…”
Section: Key Study Characteristicsmentioning
confidence: 99%
“…A randomized crossover design was used to investigate the post-prandial effects of test meals, with a 1 -week interval between testing rounds during the subjects' normal daily life. A packed test meal was systematically provided on a specified day for 6 weeks consecutively, and the details of this study were as previously reported (17,18). All subjects were provided detailed written and verbal explanations of the general purpose and procedures of the study before their written consent was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…They had sedentary clerical occupations and routine lifestyles (17,18). After recruitment, each subject was asked to complete a brief-type self-administered diet history questionnaire (BDHQ).…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations